Impact Of Coronavirus Infection (Covid-19) On Diabetic Periodontopathies - Yusupova D.U (Genius Publishing Group, 2023)
The article describes the impact of coronavirus infection on patients with diabetes mellitus, treatment of diabetic periodontitis
Keywords: coronavirus infection; COVID-19; diabetes mellitus; periodontal disease